The Influence of Transformational Leadership and Organizational Commitment on Sustainable Employee Performance with Job Satisfaction as a Mediation at PT Anugrah Tiga Berlian East Jakarta - Ferdiana, Anita; Kasmir, Kasmir (International Journal of Social and Management Studies, 2025)
This study aims to analyze the effect of transformational leadership and organizational commitment on sustainable employee performance with job satisfaction as a mediating variable. The research is motivated by the importance of achieving long-term sustainable performance through inspiring leadership, employee commitment, and job satisfaction. The study was conducted at PT Anugrah Tiga Berlian East Jakarta in 2025, involving 98 employees as respondents. A quantitative descriptive approach was applied, with data collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that transformational leadership and organizational commitment have a positive and significant effect on sustainable employee performance, both directly and indirectly through job satisfaction. Furthermore, job satisfaction plays a significant mediating role in strengthening the relationship between transformational leadership, organizational commitment, and sustainable performance.